Aggregate Spending and the Terms of Trade: Is There a Laursen-Metzler Effect? - Obstfeld, Maurice (Quarterly Journal of Economics, 1982)
This paper investigates the spending and current-account effects of terms-of-trade shifts in a model where households maximize utility over an infinite planning period. In the framework developed here, an economy specialized in production must experience a fall in aggregate spending and a current surplus as a result of an unanticipated, permanent worsening in its terms of trade. The paper's model thus provides a setting in which the current-account deficit predicted by Laursen and Metzier, Harberger, and others fails to materialize.